FARM HOUSEHOLDS IN THE REPUBLIC OF DAGESTAN - Rasulov, M A (History, Archeology and Ethnography of the Caucasus, 2016)
Farming in the Republic of Dagestan, as well as in the Russian Federation, is experiencing a difficult period in its development. Thearticle presents the dynamics of change in the number of peasant (farm) households in the republic, Russia and other regions of the North Caucasian Federal District and rates of their reductions in recent years. The author analyzes distribution of peasant (farm) households in the municipalities and urban districts of Dagestan as of July 1 and October 1, 2015, depending on natural geographic and landscape zones of the republic. The author also shows the ratio of heads of peasant (farm) households based on 1,000 residents of the subjects of the Republic of Dagestan.
Keywords: Republic of Dagestan; subjects of the Russian Federation; peasant (farm) households; number; reduction; distribution of farms; landscape zones; resident population of Dagestan.